Design of external lighting protection system for Sultan Abdul Aziz Shah (SAAS) tower / Mohd Ramzi Ahmad - Ahmad, Mohd Ramzi (2009)
Recently, Universiti Teknologi Mara (UiTM) has changed new external lightning protection system (LPS) of Menara Sultan Abdul Aziz Shah (SAAS). This new design based on Collection Volume Method (CVM). The new method believed to be providing more effective protection against lightning than before. However, these were apparently ignored by the scientific community as the CVM was considered to be a method that was proposed by a manufacturer for its own use, and hence was considered inconsequential. The aim of this paper is to design an external LPS for Menara SAAS. The design was based on the lightning protection international standard (IEC 62305) which was accepted by scientific community.